2019
DOI: 10.1002/ece3.5465
|View full text |Cite
|
Sign up to set email alerts
|

Flooding with shallow water promotes the invasiveness of Mikania micrantha

Abstract: The invasive ability of alien plants is not only affected by their biological characteristics but also by environmental factors. Therefore, investigating the relationship between plant growth and environmental factors is helpful for predicting the invasive potential of alien species. Mikania micrantha H.B.K. (a vine of Asteraceae) is one of the top 10 most invasive weeds worldwide and causes serious damage to agroforestry ecosystems. Water is an important environmental factor that affects plant growth; however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The distribution of M. micrantha covers a relatively wide array of biome types, including tropical and subtropical moist and dry broadleaf forests, tropical and subtropical coniferous forests, tropical and subtropical grasslands, deserts and xeric shrublands, savannas, and temperate broadleaf and mixed forest [23]. M. micrantha plants can grow in a variety of soil types, in both dry and cold areas, in aquatic habitats, and in broad light niches [24][25][26]. The wide range of natural habitats of M. micrantha indicates its strong adaptability to different environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of M. micrantha covers a relatively wide array of biome types, including tropical and subtropical moist and dry broadleaf forests, tropical and subtropical coniferous forests, tropical and subtropical grasslands, deserts and xeric shrublands, savannas, and temperate broadleaf and mixed forest [23]. M. micrantha plants can grow in a variety of soil types, in both dry and cold areas, in aquatic habitats, and in broad light niches [24][25][26]. The wide range of natural habitats of M. micrantha indicates its strong adaptability to different environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the gradually enhanced drought stress can pose significantly adverse impacts on plant morphological and physiological performance [21][22][23][24] as well as on SGeSGrP [25][26][27][28]. Further, the soil-water condition can trigger a noteworthy impact on the invasiveness of IAS [23,25,29]. Specifically, it is expected that drought stress potentially affects secondary metabolisms of IAS and the corresponding invasiveness especially via the variations in the secretion of allelochemicals and the corresponding allelopathy on SGeSGrP of indigenous species.…”
Section: Introductionmentioning
confidence: 99%
“…The reason that invasive plants can successfully invade habitats is closely related to their extensive ecological adaptation. Studies have shown that M. micrantha tolerates low temperature, flooding and salt stress [ 46 , 47 , 48 ], has a strong photosynthetic capacity, and tolerates a wide range of light environments [ 49 ]. Further studies have found that it not only increases the photosynthetic efficiency of stems to ensure a material basis under low light and defoliation stress, but also promoted the rapid elongation of stems by synthesizing more auxin to regulate the cell length and internode length in M. micrantha stem [ 35 , 36 , 50 ].…”
Section: Discussionmentioning
confidence: 99%